Assessing the role of aggression, empathy, and self‐serving cognitive distortions in trait emotional manipulation. (13th September 2012) - Grieve, Rachel; Panebianco, Laura
Abstract: This study extended the examination of the predictors of emotional manipulation. Participants ( N = 243) completed measures of trait emotional manipulation, emotional intelligence, social skills, psychopathy, aggression, empathy, and self‐serving cognitive distortions in a cross‐sectional correlational design. For males, higher levels of emotional intelligence, social information processing, indirect aggression, and self‐serving cognitive distortions significantly predicted emotional manipulation. For females, being younger, higher levels of emotional intelligence, indirect aggression, primary psychopathic traits, and lower levels of social awareness significantly predicted emotional manipulation. However for females, emotional intelligence acted as a suppressor. These findings support previous indications that the mechanisms behind emotional manipulation differ as a function of gender. Future research could include ability, rather than trait measures of emotional manipulation, as well as the role of context (such as intimate relationships or workplace environments), thereby allowing additional examination of the nomological network of emotional manipulation.